Information technology governance in the Malaysian electronics manufacturing industry - Tan, Khong Sin; Eze, Uchenna Cyril; Teo, Wil Ly (IBIMA Publishing, 2008)
Research indicates that information technology (IT) governance is attracting enormous attention from practitioners and academics. This is fueled by the growing importance of IT governance in the delivery of IT compliance and in its ability to create value for businesses. IT compliance minimizes risk while IT governance manages risks. This paper is a preliminary report on an electronic survey of 33 firms operating in Malaysian electronics industry. Three key frameworks underpinned the conceptual development in this paper. The findings indicate that IT governance is important to profit- and growth-oriented organisations in terms of cost efficiency, growth, asset Utilisation and business flexibility. Organisations realise the benefits of IT governance but unfamiliar with the IT frameworks. Additional implications of these findings to the electronics manufacturing industry and policy makers in Malaysia are presented.